Concrete-steel bond influence in the cyclic response of RC structural elements - Varum, H. (2007)
Poor bond conditions are a frequent cause of damage of collapse of reinforced concrete structures under cyclic loading, such as the induced by earthquakes. Reinforced concrete elements built with smooth plain reinforcing bars are particularly sensitive to bond-slip and to its effects. A simplified numerical model to account for the bond-slip effects is proposed. A numerical analysis was performed with the objective of evaluating the bond-slip influence in the dynamic response of a reinforced concrete frame, representative of existing structures built in Europe in the 50’s~70’s with smooth plain reinforcing bars. Based on the available experimental results the proposed model was calibrated.